Do Bariatric Surgeries Enhance Brown/Beige Adipose Tissue Thermogenesis? - Hankir, Mohammed K.; Seyfried, Florian (Frontiers in Endocrinology, 2020)
Bariatric surgeries induce marked and durable weight loss in individuals with morbid obesity through powerful effects on both food intake and energy expenditure. While alterations in gut-brain communication are increasingly implicated in the improved eating behavior following bariatric surgeries, less is known about the mechanistic basis for energy expenditure changes. Brown adipose tissue (BAT) and beige adipose tissue (BeAT) have emerged as major regulators of whole-body energy metabolism in humans as well as in rodents due to their ability to convert the chemical energy in circulating glucose and fatty acids into heat. In this Review, we critically discuss the steadily growing evidence from preclinical and clinical studies suggesting that Roux-en-Y gastric bypass (RYGB) and vertical sleeve gastrectomy (VSG), the two most commonly performed bariatric surgeries, enhance BAT/BeAT thermogenesis. We address the documented mechanisms, highlight study limitations and finish by outlining unanswered questions in the subject. Further understanding how and to what extent bariatric surgeries enhance BAT/BeAT thermogenesis may not only aid in the development of improved obesity pharmacotherapies that safely and optimally target both sides of the energy balance equation, but also in the development of novel hyperglycemia and/or hyperlipidemia pharmacotherapies.